2004
DOI: 10.4049/jimmunol.173.2.747
|View full text |Cite
|
Sign up to set email alerts
|

C3a and C3b Activation Products of the Third Component of Complement (C3) Are Critical for Normal Liver Recovery after Toxic Injury

Abstract: Although the complement system has been implicated in liver regeneration after toxic injury and partial hepatectomy, the mechanism or mechanisms through which it participates in these processes remains ill-defined. In this study, we demonstrate that complement activation products (C3a, C3b/iC3b) are generated in the serum of experimental mice after CCl4 injection and that complement activation is required for normal liver regeneration. Decomplementation by cobra venom factor resulted in impaired entry of hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(147 citation statements)
references
References 46 publications
9
135
1
2
Order By: Relevance
“…31 Studies have shown that C3a and C5a are capable of priming hepatocytes for regeneration, which is mediated by C3a and C5a binding to the C3aR and C5aR on Kupfer cells, a role distinct from the usual inflammatory role ascribed to C3a and C5a. 33,34 The result is consistent with the interpretation that there is more local C5a generation in the liver in the proCPB Ϫ/Ϫ mice in the peritonitis model, thus leading to enhanced liver regeneration and reduced liver necrosis.…”
Section: Discussionsupporting
confidence: 80%
“…31 Studies have shown that C3a and C5a are capable of priming hepatocytes for regeneration, which is mediated by C3a and C5a binding to the C3aR and C5aR on Kupfer cells, a role distinct from the usual inflammatory role ascribed to C3a and C5a. 33,34 The result is consistent with the interpretation that there is more local C5a generation in the liver in the proCPB Ϫ/Ϫ mice in the peritonitis model, thus leading to enhanced liver regeneration and reduced liver necrosis.…”
Section: Discussionsupporting
confidence: 80%
“…Taken together, the data reported here indicate that despite the established requirement for complement factors C3 and C5 during the hepatic regenerative response (Mastellos et al 2001;Strey et al 2003;Markiewski et al 2004), none of the traditional upstream complement activation pathways are absolutely necessary for normal liver regeneration. The most straightforward interpretation of these data is that proteolytic C3 activation during liver regeneration may occur via non-traditional mechanisms.…”
Section: Discussionmentioning
confidence: 65%
“…The results showed that hepatocellular proliferation 36 hours after partial hepatectomy, the time corresponding to peak proliferation in wildtype mice, is comparable in wildtype untreated-, wildtype mAb 1379-treated-, and C4 null mAb 1379-treated mice ( Figure 4A), indicating that disruption of all of the traditional upstream activation pathways of complement signaling does not prevent normal liver regeneration. Taken together with the observation that complement factor C3 is required for normal liver regeneration (Mastellos et Markiewski et al 2004), these data raise the possibility that C3 is activated independently of the classical-, lectindependent-, and alternative-pathways during the hepatic regenerative response. To test this possibility, C3 activation during liver regeneration was quantified in wildtype and mAb 1379-treated C4 null mice subjected to partial hepatectomy by protein immunoblot analysis of mouse plasma for the proteolytic fragment corresponding to activated C3α (Miwa et al 2007).…”
Section: Liver Regeneration and C3 Activation Occur Normally In C4-numentioning
confidence: 88%
See 1 more Smart Citation
“…18 Extract Preparation. Nuclear and whole-cell protein extracts from the liver were prepared in the presence of protease and phosphatase inhibitors as previously described.…”
Section: Methodsmentioning
confidence: 99%